RETROSPECTIVE STUDY OF PARASITE FREQUENCY IN FAECAL SAMPLES IN ROUTINE LABORATORY ANALYSIS - Serrano M., Enrique (2014)
A retrospective analysis of parasitological test results in fecal samples was done.Samples were analyzed at the Parasitology Laboratory, Faculty of Veterinary Medicineand Animal Science, Universidad Peruana Cayetano Heredia between February 2008and March 2012. Out of 476 samples, 119 (25.0%) were positive to at least one parasitespecies. Among positive samples, 71.5, 20.3 and 8.1% corresponded to protozoa,nematodes and cestodes respectively where the most frequent species were Giardiacanis (37/119) and Isospora spp (37/119).